Development and Testing of the Curiosity in Classrooms Framework and Coding Protocol - Jirout, Jamie J.; Zumbrunn, Sharon; Evans, Natalie S.; Vitiello, Virginia E. (Frontiers in Psychology, 2022)
Curiosity is widely acknowledged as a crucial aspect of children’s development and as an important part of the learning process, with prior research showing associations between curiosity and achievement. Despite this evidence, there is little research on the development of curiosity or on promoting curiosity in school settings, and measures of curiosity promotion in the classroom are absent from the published literature. This article introduces the Curiosity in Classrooms (CiC) Framework coding protocol, a tool for observing and coding instructional practices that support the promotion of curiosity. We describe the development of the framework and observation instrument and the results of a feasibility study using the protocol, which gives a descriptive overview of curiosity promoting instruction in 35 elementary-level math lessons. Our discussion includes lessons learned from this work and suggestions for future research using the developed observation tool.